Physiology study of kluyveromyces marxianus in batch culture by using xylose as sole carbon source - Aina Madia Binti Razali (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Nowadays, the most commonly utilized renewable fuel was ethanol mainly from sugar cane and starch, and thus, the consumption of these biomasses has dramatically increased. The utilization of corn starch for bioethanol production may cause a serious problem in competition with corn starch as food. Thus, a source for low-cost ethanol production would be lignocellulosic biomass such as agricultural and forestry residues were utilized. Kluyvermyces marxianus was a microorganism that possesses the capability for assimilation of many different kinds of sugars at high temperatures. In addition, this strain can grow and produce ethanol at a high temperature and is the one of the most thermotolerant among strains available. This experiment was conducted to determine the physiology of K. marxianus during batch culture with xylose as the carbon source for ethanol production. Different concentrations of xylose (70%, 30%, 50% and 70%) were used to ferment K. marxianus at 40 {03}. Growth profile of K. marxianus was analysed by using UV/VIS spectrophotometer at wavelength 600nm.